Boycotting China: More symbolic than punitive — start designing policies which support Atmanirbhar Bharat - Jha, Abhishek K.; Kumar, Anjani (Indian Express Group, 2020)
The better approach would be to start designing policies which support “Atmanirbhar Bharat”, and invest sufficiently in becoming comparable with China in terms of benefits due to economies of scale.